Structure, Thermal Behavior, and Vibrational Spectroscopy of the Silver Borate AgB3O5. Issue 3 (8th January 2015) - Sohr, Gerhard; Falkowski, Viktoria; Schauperl, Michael; Liedl, Klaus R.; Huppertz, Hubert
Abstract: The new silver borate AgB3 O5 was obtained under high‐pressure, high‐temperature conditions at 3 GPa and 600 °C in a Walker‐type multianvil device. The compound crystallizes with four formula units ( Z = 4) in the unit cell in the orthorhombic space group Pna 21 (no. 33). The lattice parameters are a = 1029.7(2), b = 832.2(2), c = 390.00(8) pm, and V = 0.3342(2) nm 3 . The new non‐centrosymmetric structure is built up from planar BO3 groups and BO4 tetrahedra, which are interconnected by two‐ and threefold‐coordinated oxygen atoms. In the channels down the c axis, the silver ions are 4+4‐fold coordinated by oxygen ions. In addition to the collection of a single‐crystal X‐ray diffraction data set, ambient‐ and high‐temperature X‐ray powder diffraction experiments as well as IR and Raman spectroscopy were performed. The vibrational spectra were interpreted though calculations of the harmonic vibrational frequencies at the Γ point. Abstract : During investigations of the Ag–B–O system, we found the light‐stable, non‐centrosymmetric silver borate AgB3 O5 . It is built from corner‐sharing BO3 and BO4 groups, which form a three‐dimensional structure. Three BO4 tetrahedra share a common, threefold‐coordinated oxygen atom in bands that are interconnected by the BO3 groups.